Two Futures Imagined in the Post-socialist Yugosphere - Vesković, Lejla (Dějiny – teorie – kritika, 2022)
The paper aims to present two proto-utopias active in the contemporary Yugosphere. It takes two novels as the representatives of those two juxtaposed narratives – Saša Ilić’s The Dog and the Double Bass and Peter Handke’s A Journey to the Rivers: Justice for Serbia. Hanke’s novel is being treated as a representative of a nationalist realist literary tradition codified by Dobrica Ćosić marked by self-victimization and self balkanization, the concept of genocide, elements of camp literature, orientalization and demonizing of the Other, theories of neo-pagan conspiracy, belief in the historical mission to be “antemurale Christianitatis” but also a belief of having a mission to revive decadent Europe with barbarogenius spirit. As I agrue this tendency was strengthened by Emir Kusturica’s foreword to the novel, whereas in the very novel only orientalization and balkanization can be recognized. Ilić’s novel is treated as a representative of a socialist modernist tradition and the canon established by Krleža and especially Kiš. The common characteristics of the identified literary genre present in the novel are the revaluation of nationalist canon, criticism of the wartime past, struggle to overcome traumas of the wartime past, imposing question of guilt and responsibility for the bloody dissolution of the former Yugoslavia, advocating secular and cultural tradition of socialist enlightenment but also revaluation of the totalitarian practices of the former socialist regime, the evident influence of western popular culture, the reverberation of the former so-called “non-alignment policy” and also criticism of the class divided and profit-driven predominantly western system of values. Two mentioned homogenized narratives currently take turns in overtaking public imagination. Future will show which future will prevail.